Comparison Study of Braden Scale and Time-to-Erythema Measures in Long-term Care. Issue 5 (September 2015) - Yap, Tracey L.; Rapp, Mary Pat; Kennerly, Susan; Cron, Stanley G.; Bergstrom, Nancy
Abstract : PURPOSE: The Braden Scale for Predicting Pressure Sore Risk is used to assess risk, and the Centers for Medicare & Medicaid guidelines suggest the use of a tissue tolerance procedure that detects time-to-erythema (TTE) to further refine tissue tolerance, a component of the Braden Scale. The aim of this study was to compare the Braden Scale and TTE as risk classification methods and their utility in identifying care planning interventions. DESIGN: Descriptive study using retrospective chart review. SUBJECTS AND SETTING: Participants were a convenience sample of 89 adults 65 years or older residing in a long-term care facility in the Midwestern United States. The sample was drawn from a facility-generated list of 90 residents who had both Braden Scale and tissue tolerance testing performed within 24 hours of admission from any setting, readmission after a hospital stay, or performed as part of a routine annual reassessment. METHODS: Results of staff performance on the Braden Scale and TTE were compared as risk classification methods and based on their utility for identifying care planning interventions. Data were collected during 1 session when TTE and the Braden Scale were completed. Agreement between the 5 risk categories from the Braden Scale and 5 TTE risk categories was analyzed via the kappa statistic and Kendall tau-c statistic. Spearman or Pearson correlation coefficients were calculated as appropriate for ordinal and continuous risk, intervention, and severity measures. RESULTS: The mean Braden Scale score was 17.5 ± 3 (mean ± SD); the mean TTE-Bed was 2.35 ± 0.57 hours and the mean TTE-Chair was 2.18 ± 0.52. Using a Braden Scale score of 18 or less as a cut point for identifying clinically relevant risk for pressure ulcer development, 55 participants were deemed at risk, 62 had mobility subscale scores less than 4, 76 had activity subscale scores less than 4, and 73 were incontinent. The weighted kappa statistic demonstrated weak agreement between TTE-Bed and the Braden Scale Total Score (κ = 0.04; 95% CI: 0.002-0.07). Agreement was not significant for TTE-Chair and the Braden Scale Total Score (κ = 0.01; 95% CI: −0.01 to 0.04), TTE-Bed and Braden Scale-Mobility (κ = 0.09; 95% CI: −0.05 to 0.23) and between TTE-Chair and Braden Scale-Activity (κ = 0.07; 95% CI: −0.05 to 0.19). The TTE-Chair and TTE-Bed assessment demonstrated fair agreement (κ = 0.37; 95% CI: 0.19-0.55). The Braden Scale cumulative score where a lower score equates to higher risk was found to be correlated with the total number of interventions observed in the care plan ( r = −0.62; P < .0001). Correlation between the Braden Scale-Mobility subscale score and in-bed mobility specific interventions was r = −0.64 ( P < .0001), whereas correlation for TTE-Bed category and specific in-bed mobility interventions was r = 0.21 ( P = .05). CONCLUSION: Study findings provide little support for tissue tolerance testing versus assessment using the validated Braden Scale for assessment of pressure ulcer risk. Study findings support the use of the Braden Scale to develop an individualized care plan based on the areas of risk.